A Rapid and Sensitive Diagnostic Screening Assay for Detection of Mycobacteria Including Mycobacterium tuberculosis Directly from Sputum without Extraction. (6th January 2015) - Cross, Lisa Jane; Anscombe, Catherine; McHugh, Timothy D.; Abubakar, Ibrahim; Shorten, Robert John; Thorne, Nicola; Arnold, Cath
Abstract : We report a novel approach utilising a real-time PCR screening assay targeting a 53 bp tandemly repeated element present at various loci within the Mycobacterium tuberculosis (Mtb) genome. Positive samples were identified within a discriminatory melting curve range of 90–94°C, with results obtained in under one hour directly from decontaminated sputum samples without extraction. A panel of 89 smear-positive sputa were used for analytical validation of the assay with 100% concordance, with sensitivity matching that of culture. Cross reactivity was detected within a narrow range of mycobacteria other than tuberculosis (MOTT) (five sputa, three in silico ), with the highest sensitivity within M. avium complex (MAC). A year-long head to head evaluation of the test with the GeneXpert platform was carried out with 104 consecutive samples at the Royal Free Hospital, UK. Receiver operating characteristics (ROC) analysis of the data revealed that the two tests are approximately equivalent in sensitivity, with the area under the curve being 0.85 and 0.80 for the GeneXpert and our assay, respectively, indicating that the test would be a cost effective screen prior to GeneXpert testing.